Analisis Kelayakan Usaha Wisata Ecovillage Desa Silimalombu - Darwin Damanik; Pawer Darasa Panjaitan; Fariaman Purba; Pandapotan Damanik; Bosma Sinaga (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
The rapid development of the tourism sector and the business sector in North Sumatra, one of which is Samosir, is a factor in the increasing demand and needs of local and foreign tourists. This research aims to analyse the business feasibility of Silimalombu Village Ecovillage. This research uses SWOT analysis to analyze the development strategy. Technical data analysis used in this research is by means of interviews, observation and documentation. The method used in this research is descriptive quantitative analysis. To analyse the financial aspects, the Net Present Value, IRR and Gross B/C Ratio methods were used. While to assess other aspects, factors that are considered important in the assessment are used. The result of this research is that Silimalombu Village Ecovillage is feasible to run and develop. After being analysed using investment criteria, the results found are Gross B / C Ratio 1.69> 1, Net Benefit Cost Ratio 2.63> 1 Probitability Ratio> 1, Net Present Value, 1,682.7> IRR 34%, meaning that the Go project is feasible.